Local Fiscal Response to Intergovernmental Transfers - Slack, Enid (The Review of Economics and Statistics, 1980)
A N extensive literature has developed on the impact of intergovernmental transfers on the budgetary decisions of state and local governments. In the more recent studies, models of fiscal response based on consumer utility maximization models are derived and tested, usually on a cross-section data base.1 The model in this paper, along the lines of previous work, analyzes the budgetary response of local governments in Ontario, Canada to provincial transfers, using pooled cross-section data for upper-tier municipalities in 1973 and 1974.2 This study differs in a number of important respects from most other studies on the expenditure response to grants. Firstly, it analyzes the impact of provincial grants on local government expenditures in both price and income terms. Grants are divided into two categories depending on whether they are anticipated to have only an income effect (as in the case of unconditional non-matching grants) or both price and income effects (as with conditional matching grants).3 In the model derived in this paper, grants are treated as endogenous and the estimation procedure takes account of the interrelationship between grants and expenditures. Both a Stone-Geary utility function and a translog indirect utility function are used to derive expenditure demand equations. Finally, this study attempts to incorporate specific institutional features of the provincialmunicipal fiscal system into the theoretical model. The model is derived in the next section, the discussion of data and estimation and the empirical results are presented in the following section and some conclusions are drawn in the final section of the paper.